A Numerical Investigation of Variably Heated Enclosure to Enhance its Heat Transfer Rate using CFD. Issue 1 (September 2020) - Ragupathi, P.; Aravind, S.; Kumar, D. Sathish; Vignesh, G.
Abstract: The flow simulation with the help of computational tools helps in solving many engineering problems related to fluid dynamics. This in turn reduces the time and cost incurred in doing real time experimental investigations. In this present research work, computational investigation was carried out in a variably heated enclosure to enhance the life span of the electronic components inside the enclosure. The investigation was performed over a twilight enclosure system, the purpose of this system is switch on or off the street lights with support of sensors automatically. This particular enclosure is subjected to heating as it is continuously exposed to sunlight through the day. This enclosure consists of delicate electronic components which are sensitive to heat. The heat transfer can be enhanced in this system by the prevailing natural flowing air in the surrounding by free convection process. To enhance and optimize this heat transfer process, numerical simulation using computational tools was carried out by changing the physical layout of the enclosure. To perform this numerical simulation, flow simulation module available in the SolidWorks was used. Also, to model this system, the same modeling software was used. From the outcome of this numerical flow simulation, it showed a drop of 36.3% in the heat transfer rate when compared to the existing model to the proposed model used for the simulation. By using the modified and proposed model, the life span of the entire system will be improved.